Obsessive compulsive symptoms in patients with primary generalized and partial onset epilepsy - Lavania, Sagar; Siddiqui, Mohd. Aleem; Bharti, Shantanu; Kumar, Abhishek (International Journal of Research in Medical Sciences, 2018)
Background: To find out and compare the obsessive-compulsive symptoms / disorder among patients of primary generalized and partial onset epilepsy. Methods: Patients with epilepsy diagnosed clinically at psychiatric out patient’s department were selected for the study and categorized as primary generalized onset tonic clonic seizure type and partial onset seizure. Yale-Brown obsessive-compulsive symptoms check list and scale was applied to find out the obsessive-compulsive symptoms. Results: A total of 110 patients were categorized as primary generalized (GE) 49 and partial onset epilepsy (PE) 61 patients. Obsessive-Compulsive Symptoms (OCS) were found to be 19.9%, and OCD among 3.63%. Mean Y-BOCS scores for obsession were found to be 3.77±1.93 and 4.93±2.03, (t = -3.034, df= 108, p= .003). Whereas the mean Y-BOCS compulsions score was 2.93±1.96 and 4.62±1.87 was (t = -4.590, df= 108, p= .000) for GE and PE group respectively. Conclusions: OCD and OCS among the epilepsy patients were found to be 3.63%, and 19.9% respectively, and significantly higher mean obsessive and compulsive score were found for the group of partial onset epilepsy.